Elaboração de pictogramas para usuários de medicamentos do Sistema Único de Saúde de um município da região central do sul do Brasil - Alves, Wagner Naysinger (2022)
Medical prescription is a fundamental tool for the success of drug therapy and, therefore, its understanding is directly related to therapeutic adherence and the correct use of drugs. In this context, pictograms are a communication tool capable of reducing the understanding deficit and facilitating the interpretation of the medical prescription. The objective of the study was to develop and test the legibility of pictograms related to the health area, in order to contribute to the understanding and adherence to therapeutic regimens of SUS users. This is a descriptive study, with a qualitative and quantitative approach, developed in a Health Unit, located in the municipality of Formigueiro - RS. Two focus groups were held to create the pictograms, one formed by health professionals and the other by SUS users. After elaboration, the pictograms were submitted to a readability test. For data collection, a questionnaire containing questions related to sociodemographic variables was used, and the pictograms were drawn up, with verification of the understanding of the figures presented. Of the five pictograms submitted to the readability test, four were legible and one was not, due to its complexity. Among the participants in the readability survey, there was a prevalence of females (65%), of mature age (33.8%), with high school education (40.5%). Most of those surveyed (50%) have an income of one to three minimum wages, are professionals (24.1%) from group 2 (day laborer, domestic worker, caregiver for the elderly, etc.) and use (56%) one to three medications a day. Understanding the pictograms was associated with schooling, occupation and number of daily medications. The implementation of pictograms in pharmacological treatment, associated with verbal guidelines, can promote better understanding and adherence to treatment, contributing to the rational use of medications.